2022
DOI: 10.3389/fimmu.2021.795260
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils Lose the Capacity to Suppress T Cell Proliferation Upon Migration Towards Inflamed Joints in Juvenile Idiopathic Arthritis

Abstract: Neutrophils are highly abundant in synovial fluid of rheumatic inflamed joints. In oligoarticular juvenile idiopathic arthritis (JIA), synovial fluid neutrophils have impaired effector functions and altered phenotype. We hypothesized that these alterations might impact the immunoregulatory interplay between neutrophils and T cells. In this study we analyzed the suppressive effect of neutrophils, isolated from blood and synovial fluid of oligoarticular JIA patients, on CD4+ T cells activated by CD3/CD28 stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…In addition, ROS are necessary in suppression of T-cells. Therefore, lack of this suppression may contribute to local inflammations and autoimmune reactions ( 47 ). Hence, the link between recent PPI exposures, neutrophil's ROS production, and the onset of ADs require further studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ROS are necessary in suppression of T-cells. Therefore, lack of this suppression may contribute to local inflammations and autoimmune reactions ( 47 ). Hence, the link between recent PPI exposures, neutrophil's ROS production, and the onset of ADs require further studies.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies report that blood NDGs must be activated to exhibit MDSC function (4)(5)(6)(7)(8). However, we and other authors have observed inhibitory capacities without neutrophil activators (12,21,22). In our previous study, we showed that NDGs are not activated during the isolation process, but become activated approximately one hour after coincubation with activated T-cells, as measured by the surface expression of the neutrophil activation markers CD11b and CD66b (21).…”
Section: Discussionmentioning
confidence: 84%
“…SF polarization of healthy monocytes does not replicate the increased co-stimulatory capabilities observed in the patients’ synovial monocytes; nor does it induce a decrease in ROS production and phagocytosis, as previously observed (7). We have recently shown that migration through a transwell system influences the effector functions of neutrophils (8). To determine how the patient’s synovial monocytes may acquire the remaining features, we investigated the effect of migration through an artificial synovial membrane towards SF on healthy monocytes ( supplementary figure 5A ).…”
Section: Resultsmentioning
confidence: 99%
“…Here, we confirmed that synovial monocytes express high levels of co-stimulatory markers and further showed that the monocytes induce proliferation and activation of T-cells. We have recently shown that synovial neutrophils lose their capacity to suppress T-cell proliferation, and that healthy neutrophils lose this ability upon migration (8). Thus, an increase in activation of T-cells by monocytes, and a loss of suppressive capability by neutrophils may explain the expansion and activation of T-cells within the joint of patients with oJIA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation